Kapitał intelektualny jako składnik zasobów przedsiębiorstwa - Smok, Barbara (Intellectual Capital as a Part of the Enterprise Assets, 2006)
Nowadays the economy is deeply based on knowledge. It uses knowledge in processes of creali, distribution and application. Knowledge as well as the intellectual capital are one of the most valuable assets within the enterprise. Modern enterprises need new production factors in shape of a w asset that is intellectual capital. It is very important with the dynamically changing markets. This per has been devoted to this issues.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1121, s. 141-151